The Attitudes of Fine Arts High School Students Toward Turkish Music Theory and Practice Course - Alay, Aslı Yeşilgül; Kara, Nadir (Ege Üniversitesi, 2025)
This study aims to examine the attitudes of Fine Arts High School music department students toward the Turkish Music Theory and Practice course in terms of demographic and contextual variables. Grounded in the premise that students’ attitudes significantly shape their academic success and motivation, the research evaluates how this course, which integrates theoretical knowledge and practical skills within an interdisciplinary framework, contributes to students’ musical development. A causal-comparative design was used in this study, which was supported by a literature review. Also, quantitative methods were utilized in this study by using SPSS 21.0. analysis program and analyzing the data through t-tests and one-way analysis of variance. Confirmatory Factor Analysis, conducted with AMOS 26, validated the structural integrity of the measurement scale, with model fit assessed through goodness-of-fit indices. The findings reveal that students’ attitudes toward the course vary significantly, influenced by factors such as gender, study habits, and satisfaction with course hours, while grade level, age, prior experiences and teacher changes showed no significant effect. These results underscore the critical role of individual differences in shaping attitudes toward music education and show the importance of contributing to the literature by demonstrating how specific contextual factors mediate students’ engagement with the Turkish music curriculum. It can be said as a proposal, to enhance this engagement, educators should design personalized learning strategies that address gender-specific needs and study habits to foster positive attitudes toward the course.

Bu çalışma, Güzel Sanatlar Lisesi müzik bölümü öğrencilerinin Türk Müziği Teori ve Uygulama dersine yönelik tutumlarını, demografik ve bağlamsal değişkenler açısından incelemeyi amaçlamaktadır. Öğrencilerin tutumlarının akademik başarılarını ve motivasyonlarını önemli ölçüde şekillendirdiği anlayıştan yola çıkan araştırma, teorik bilgi ve pratik becerileri disiplinler arası bir çerçevede bütünleştirerek bu dersin öğrencilerin müzikal gelişimlerine nasıl katkı sağladığını değerlendirmiştir. Literatür taramasıyla desteklenen bu çalışmada nedensel karşılaştırmalı bir tasarım yöntemi kullanılmıştır. Ayrıca bu çalışmada, veriler SPSS 21.0 analiz programı kullanılarak, t-testleri ve tek yönlü varyans analizi yoluyla analiz edilerek niceliksel yöntemlerden yararlanılmıştır. AMOS 26 ile gerçekleştirilen Doğrulayıcı Faktör Analizi, uyum iyiliği indeksleri aracılığıyla model uyumu değerlendirilmiş ve böylece ölçüm ölçeğinin yapısal bütünlüğü doğrulanmıştır. Bulgular, öğrencilerin derse yönelik tutumlarının cinsiyet, çalışma alışkanlıkları ve ders saatlerinden memnuniyet duyma gibi faktörlerden etkilenerek önemli ölçüde değiştiğini, ancak sınıf düzeyi, yaş, önceki deneyimler ve öğretmen değişikliklerinin anlamlı bir etki göstermediğini göstermiştir. Bu sonuçlar, bireysel farklılıkların müzik eğitimine yönelik tutumları şekillendirmedeki kritik rolünü vurgulamış ve belirli bağlamsal faktörlerin öğrencilerin Türk müzik müfredatına katılımına nasıl aracılık ettiğini göstererek literatüre katkıda bulunmanın önemini ortaya koymuştur. Öneri bağlamında denilebilir ki bu katılımı artırmak için eğitimciler, derse yönelik olumlu tutumları teşvik etmek amacıyla cinsiyete özgü ihtiyaçları ve çalışma alışkanlıklarını ele alan kişiselleştirilmiş öğrenme stratejileri tasarlayabilmelidirler.
GÜZEL SANATLAR LİSESİ ÖĞRENCİLERİNİN TÜRK MÜZİĞİ TEORİ VE UYGULAMA DERSİNE YÖNELİK TUTUMLARI
Keywords: Performing Arts (Other); Performans Sanatları (Diğer)